Chestnut shells (Italian cultivar "Marrone di Roccadaspide" PGI): Antioxidant activity and chemical investigation with in depth LC-HRMS/MSn rationalization of tannins. (March 2020) - Cerulli, Antonietta; Napolitano, Assunta; Masullo, Milena; Hošek, Jan; Pizza, Cosimo; Piacente, Sonia
Graphical abstract: Highlights: The MeOH extract showed anti-inflammatory and antioxidant activity in in vitro tests. LC-ESI/LTQOrbitrap/MS/MS n analysis highlighted the occurrence of 88 compounds. Phenolic and triterpene derivatives were isolated and identified by 1D- and 2D-NMR. 11 main compounds were quantitatively determined by LC-ESI/QTrap/MS/MS. Bioactivity and metabolite profile of EtOH:H2 O extract were similar to MeOH extract. Abstract: In Italy a particularly valuable chestnut is "Marrone di Roccadaspide", a protected geographical indication (PGI) product, deriving from a Castanea sativa cultivar, typical of Salerno province in Campania region. As chestnut industrial processes yield a large amount of shell by-products, in this study the possibility to retrain this waste food as potential source of bioactives was investigated. The ability of "Marrone di Roccadaspide" shell MeOH extract to modulate the pro-inflammatory transcriptional factor NF-κB after LPS stimulation, along with the antioxidant activity by a cell-based in vitro test, were evaluated. To correlate the NF-κB inhibition (67.67% at 5 μg/mL) and the strong antioxidant activity to the chemical composition, an analytical approach based on LC-ESI/LTQOrbitrap/MS/MS n along with NMR characterization of isolated compounds was developed. The identification of hydrolysable and condensed tannins, along with flavonoids, phenol glucosides, ellagic acid derivatives, and triterpenoids was accomplished. The most representative compounds were quantitatively analyzed by LC-ESI/QTrap/MS/MS, showing bartogenic acid as the compound occurring in the highest amount (103.08 mg/100 g shells). With the aim to explore the possibility to employ chestnut shells as suitable source of bioactives for the preparation of functional ingredients, the chemical composition and the antioxidant activity of "eco-friendly" extracts (EtOH and EtOH:H2 O 7:3) was finally evaluated, showing a high superimposability of the EtOH:H2 O (7:3) extract to the MeOH extract.